A Hybrid Windowless Dual Tube Solar Reactor for Continuous Volumetric Natural Gas Dissociation - Rodat, Sylvain; Abanades, Stéphane (Frontiers in Energy Research, 2020)
Solar natural gas thermal dissociation, producing both hydrogen and solid carbon, appears as a promising way for progressive decarbonization of the world energy mix. Three main challenges remain to be tackled: carbon deposition issue, continuous round the clock operation of the solar reactor with an intermittent energy resource, and technology scale-up. The present work proposes a new windowless scalable solar reactor enabling volumetric gas-phase (i.e., not at the walls) methane cracking with possible hybridization. CFD simulations demonstrate the advantage of the new concept as compared to conventional tubular reactors. The proposed system uses a hot inert gas to generate a high temperature fluid zone similar to a combustion flame where the methane decomposition occurs. Based on the numerical model developed, a sensitivity study is carried out in order to optimize the reactor design enabling both high methane conversion and low carbon deposition. For methane flow-rates of 4.6 × 10–6 kg.s–1 and 2.3 × 10–6 kg.s–1 (argon flow-rate of 9.3 × 10–5 kg.s–1), methane conversion reached 46 and 73% for maximum fluid zone temperatures of 1676 and 1750 K, respectively. Furthermore, electric hybridization is investigated in order to highlight the potential for day and night continuous operation. Indeed, since an inert carrier gas is used as heat transfer medium, it can be heated by different energy sources to maintain the thermal power input during low irradiation periods. Thus, the solar flame concept that we previously patented proves to be of interest for practical implementation to introduce solar heat into high temperature processes.